The mosses of Sungai Rawog conservation area, Segaliud Lokan forest reserve, Sabah, Malaysia - Monica Suleiman; N. J. Rajian; A. Irmah; M.A.M. Andi (Sabah Forestry Department, 2019)
A total of 50 species, in 26 genera and 13 families, of mosses were collected from Sungai Rawog Conservation Area within the Segaliud Lokan Forest Reserve. This represents ca. 8% of the taxa of mosses reported for Sabah and ca. 7% of the taxa reported for Borneo. The largest family of mosses collected was Calymperaceae with 17 species, followed by Pylaisiadelphaceae with seven species. These families of mosses are typically common in lowland tropical rain forests. It is worth to note that two of the species collected, Leucobryum candidum (Brid. ex P. Beauv.) Wilson. and Wijkia polymorpha (Dixon) H.A. Crum., are new records for Sabah. This shows that this area is an important habitat for lowland species of mosses in Sabah.